2009
DOI: 10.1080/00207590701656770
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between three types of aggression and peer relations in elementary school children

Abstract: Previous studies have repeatedly found that aggression causes various internalizing and externalizing problems. Despite the robust relationship, exactly how aggression causes these problems remains unclear, although it is plausible to postulate that this occurs both directly and indirectly (via other behavioural factors). One possible indirect factor might be the aggravation of peer relations. The poor peer relations of aggressive children could make them isolated psychologically or physically from peers, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Specifically, the study's data indicated that the children with few friends had significantly higher withdrawn/depressed scale scores. Yamasaki and Nishida () reported that children with fewer friends showed significantly more aggressive behaviors than did those with many friends (Yamasaki & Nishida). Next, lower levels of parental HRQOL were significantly associated with internalizing and externalizing problems in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the study's data indicated that the children with few friends had significantly higher withdrawn/depressed scale scores. Yamasaki and Nishida () reported that children with fewer friends showed significantly more aggressive behaviors than did those with many friends (Yamasaki & Nishida). Next, lower levels of parental HRQOL were significantly associated with internalizing and externalizing problems in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the term relational aggression is used throughout the present study, our review of the literature includes findings from studies examining each of these constructs, given their high similarity. Relational aggression has been associated with a greater number of friends relative to physical aggression (Yamasaki & Nishida, 2009). Physically aggressive children may be less desirable as friends, because associating with them may involve risk of physical conflict and injury (Grotpeter & Crick, 1996).…”
Section: Distinctions Between Physical and Relational Aggressionmentioning
confidence: 99%
“…The dimensions of VAO BIM climate in the internal process model were peer relations and focus on others. Originating from relationships in the workplace, and supported by friends and trust, peer relations are measured by indicators involving high-quality relationships (Kaewpan et al, 2017), support from colleagues (Reich & Benbasat, 1996;Yamasaki & Nishida, 2009), and trusting colleagues (Parker et al, 1995). When implementing BIM in construction projects, the aforementioned indicators are reflected by obtaining quality of relationships through BIM (OQR-BIM), receiving more colleagues' support through BIM (RCS-BIM), and increasing trust in colleagues (ITC-BIM).…”
Section: Initial Indicators In Internal Process Modelmentioning
confidence: 99%
“…Peer relations Obtaining quality of relationships through BIM OQR-BIM Kaewpan et al 2017Receiving more colleagues' support through BIM RCS-BIM Reich and Benbasat (1996), Yamasaki and Nishida (2009) Increasing trusts in colleagues ITC- BIM Parker et al (1995) Focus on Others West et al (1998) Work innovation through BIM WI- BIM Hülsheger et al (2009) Learning from each other through BIM LEO-BIM Kivimaki and Elovainio (1999) Understanding task criteria with BIM UTC-BIM Kivimäki et al (1997) Hierarchical influence Documenting power and responsibility with BIM DPR-BIM Dahl and Olsen (2013) Perceiving less authoritarian PLA-BIM Payne and Mansfield (1973) Goal effectiveness…”
Section: Participationmentioning
confidence: 99%